Harrison's manual of medicine - Kasper, Dennis L.; Fauci,Anthony S.; Hauser, Stephen L.; Longo, Dan L.; Jameson, J. Larry; Loscalzo, Joseph (bMcGraw-Hill Medical Publishing Division, 2016)
Suitable for use at the point of care, this manual covers every area of clinical medicine, including: etiology and epidemiology; clinically relevant pathophysiology; signs and symptoms; differential diagnosis; physical and laboratory findings; therapeutics; and, practice guidelines